2010
DOI: 10.1371/journal.pone.0010053
|View full text |Cite
|
Sign up to set email alerts
|

FAM5C Contributes to Aggressive Periodontitis

Abstract: Aggressive periodontitis is characterized by a rapid and severe periodontal destruction in young systemically healthy subjects. A greater prevalence is reported in Africans and African descendent groups than in Caucasians and Hispanics. We first fine mapped the interval 1q24.2 to 1q31.3 suggested as containing an aggressive periodontitis locus. Three hundred and eighty-nine subjects from 55 pedigrees were studied. Saliva samples were collected from all subjects, and DNA was extracted. Twenty-one single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
0
24
1
Order By: Relevance
“…DNA integrity was checked and the allelic discrimination of TBX21-1993T/C SNP (rs4794067) variants was performed in 3 mL reactions using Taqman (Applied Biosystems, Warrington, UK) chemistry as previously described. 48,49 Genotyping was performed blinded to group status. For reaction quality control, a sample of known genotype was included in the plate and a no DNA template sample was included as negative control.…”
Section: Methodsmentioning
confidence: 99%
“…DNA integrity was checked and the allelic discrimination of TBX21-1993T/C SNP (rs4794067) variants was performed in 3 mL reactions using Taqman (Applied Biosystems, Warrington, UK) chemistry as previously described. 48,49 Genotyping was performed blinded to group status. For reaction quality control, a sample of known genotype was included in the plate and a no DNA template sample was included as negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The BRINP3 gene has been correlated with myocardial infarction 60 and aggressive periodonitis 61 in genetic studies. It has been postulated that it could play a role in osteoblast differentation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of most studies implicate FAM5C as a disease marker, although the association between FAM5C and periodontitis is controversial [8], [18]. However, the contribution of FAM5C to the phenotype of each disease remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An association between the expression of FAM5C and tongue squamous cell carcinoma [5], the hypermethylation of the FAM5C gene in gastric cancer [7], and a genetic association between polymorphisms within the FAM5C gene and aggressive periodontitis [8] have been reported. A genome-wide association study identified a genetic association between polymorphisms within the FAM5C gene and myocardial infarction, thereby implicating FAM5C as a risk factor for myocardial infarction [9].…”
Section: Introductionmentioning
confidence: 99%